2022
DOI: 10.4178/epih.e2022023
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends and related factors in leisure-time sedentary behavior among Koreans: an analysis of data from the 2011-2017 Korea Community Health Survey

Abstract: Objectives: This study identified trends in leisure-time sedentary behaviors on weekdays, as well as characteristic sociodemographic and lifestyle correlates in Korean adults. Sedentary behavior has gradually increased and has become a public health problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(74 reference statements)
1
2
0
Order By: Relevance
“…Our results showed that only approximately a quarter of middle-aged or older workers in Korea engaged in 150 min or more per week of physical activity, which is in line with the findings of previous Korean studies 28 29. As it is a well-known fact that the risk of physical inactivity increases with age,30 the low prevalence of physical activity among middle-aged or older workers observed in our study suggests that active policy intervention to promote physical activity is required.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that only approximately a quarter of middle-aged or older workers in Korea engaged in 150 min or more per week of physical activity, which is in line with the findings of previous Korean studies 28 29. As it is a well-known fact that the risk of physical inactivity increases with age,30 the low prevalence of physical activity among middle-aged or older workers observed in our study suggests that active policy intervention to promote physical activity is required.…”
Section: Discussionsupporting
confidence: 92%
“…The CHS is a nationwide population-based survey among community-dwelling adults aged 19 years and older to assess community health promotions conducted by the Korea Disease Control and Prevention Agency (KDCA) since 2008. The survey uses a complex, multistage, stratified sampling design to collect information related to health status, health behaviours, healthcare utilisation and health determinants to ensure the representativeness of the Korean census 17…”
Section: Methodsmentioning
confidence: 99%
“…The survey uses a complex, multistage, stratified sampling design to collect information related to health status, health behaviours, healthcare utilisation and health determinants to ensure the representativeness of the Korean census. 17 …”
Section: Methodsmentioning
confidence: 99%